LO051: Validation of a clinical decision rule to detect patients with adverse drug events in the emergency department. (2nd June 2016) - Hohl, C.M.; Badke, K.; Wickham, M.E.; Zhao, A.; Sivilotti, M.; Perry, J.J.
Abstract : Introduction: Adverse drug events (ADE) are a leading cause of emergency department (ED) visits, yet are missed in up to 50% of presentations. In 2014, Accreditation Canada, a not-for-profit organization that evaluates healthcare institutions based on quality of care, introduced a requirement for EDs to identify patients at high-risk for drug-related morbidity, so that medication management interventions can be targeted to high-risk groups. We derived a clinical decision rule to identify patients at high-risk for ADEs using 4 variables. Our objective was to validate the rule by determining its sensitivity and specificity in a new sample.Methods: We conducted a prospective observational study in two tertiary care and one urban community hospital in British Columbia and Ontario. We used a systematic selection algorithm to generate a representative sample, and enrolled adults who reported taking at least one medication during the prior two weeks. Nurses completed the clinical decision rule and evaluated patients for standardized clinical findings. Each patient was assessed by a research pharmacist and a physician who were blinded to data collected by nurses. Any disagreement was subsequently adjudicated by an independent committee. The primary outcome was an ADE, defined as an unintended and harmful event related to medication use resulting a change in medical management, hospital admission or causing death. We calculated the rule's sensitivity, specificity, and the proportion of patients screening positive with 95% confidence intervals (CI).Results: Among 1529 enrolled patients, 196 (12.8%, 95% CI 11.2-14.6%) were deemed to have experienced an ADE. The rule, consisting of the variables (i) having a pre-existing medical condition or having taken antibiotics within one week, and (ii) age ≥ 80 or having a medication change within 28 days, had a sensitivity of 92.9% (95%CI 88.3%-96.0%) and a specificity of 35.0% (95%CI 32.5%-37.7%) for ADEs. The proportion of patients screening positive was 41.7%.Conclusion: Among adults presenting to EDs, the rule was sensitive for ADEs while maintaining reasonable specificity. If implemented, the rule may help identify those patients at high-risk for ADEs who may benefit from evaluation by a clinical pharmacist in the ED, and will help institutions meet current Accreditation Canada standards.